Protein stability study with respect to mutation in Brassica juncea, Brassica rapa and Brassica napus (Journal of Oilseed Brassica, 2026)
In the present study Brassica juncea, B. rapa, B. napus and their accessions lines of M5 generation were analyzed in M6 generation for protein profiling through sodium dodecyle sulphate (SDS)–PAGE. SDS–PAGE with some modifications the resolution capacity of small molecular mass protein less than 20 kDa were separable with the used technique. The banding pattern of protein of rapeseed-mustard and their accessions have variable molecular, weight bands extend from 9 to 65 kDa. The total 50 bands obtained in which 43 bands were polymorphic, 7 bands were unique and 7 were monomorphic in rapeseed-mustard and their accessions. The B. juncea var. Bio-902, 3321, 666, GPT1 has unique protein bands. The value of similarity among different cultivars fluctuates between 0.26 to 1.0. The highest similarity value was observed 0.68 in B. napus. The lowest similarity value was recorded 0.26 in B. juncea accession (427-2). After studying the M6 generation of rapeseed-mustard soluble seed protein revealed some differences among the species in terms of the number, position and intensity of bands, while accession discrimination based on SDS-PAGE was also done. Based on polymorphic and unique bands there was 86 % polymorphism among the rapeseed-mustard and their accessions.